Impactos econômicos do vale-cultura: uma abordagem em equilíbrio geral computável - Gustavo Fernandes Souza (2016)
Consumption Restrictions are one of the biggest problems faced by cultural sector in Brazil. Brazilian government launched the Vale-Cultura to alleviate this problem. Its a voucher system in which the individual eligible for the program receive an extra income to be used exclusively in the purchase of cultural goods and services, defined in a previous list. The objective of this study is to analyze the impacts of Vale-Cultura in the cultural sector and the economy as a whole. We use a large-scale computable general equilibrium (CGE) model of Brazil (BRIDGE). The impact on the urban space is analyzed in nine major metropolitan areas of Brazil, using data from the Brazilian Family Budget Survey (POF) from 2008-2009. The main results of the simulations, analyzed in relation to a scenario without the Vale-Cultura, estimated a GDP growth, mainly driven by the increase in household consumption on the side of absorption. The change in consumption is positive for beneficiaries in the sectors in which they are the items of the cultural sector. The welfare analyzed by the equivalent variation and compensating variation in income, shows positive growth for the voucher recipients. Indirect taxes and the production taxes are also affected positively due to the various effects on the economy, which partly offset the transfer of government enterprises through tax waiver. Finally, in terms of sectoral analysis, there was a positive growth in the activity level of cultural industries and negative in some other, showing a reallocation of productive factors and increased cost of production. These results suggest that this voucher system has a great potential in social and economic terms.